(untitled) (Journal of the College of Basic Education, 2025)
The aim of the current research was to identify moral anxiety among kindergarten students. The research sample included (400) kindergarten students. The researcher used a descriptive and analytical approach in her research. To achieve the research objectives, she relied on a moral anxiety scale based on Dahesh’s (2010) definition. The scale includes 30 items divided into four comprehensive domains: guilt, morality, fear, and shame. Statistical methods were used to assess the research objectives, including Pearson’s correlation coefficient, Cronbach’s alpha coefficient for reliability, a t-test for two independent samples, and a t-test for one sample. The researcher concluded that kindergarten students do not experience moral anxiety.